Perceived value and tourist donation intentions at religious heritage sites: the mediating roles of awe and subjective well-being - Yu, Shuo; Li, Xi; Cao, Yu (Frontiers in Psychology, 2025)
IntroductionReligious heritage tourism is increasingly recognized for its dual contribution to cultural preservation and economic sustainability. However, the psychological mechanisms that drive tourists' willingness to donate at religious heritage sites remain underexplored. Building on the Stimulus-Organism-Response (SOR) theory, this study investigates how tourists' perceived value shapes their donation intentions, highlighting the mediating roles of awe and subjective wellbeing, as well as the moderating role of religiosity.MethodsData were collected from 529 visitors to the A-Ma Temple in Macau. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to test the hypothesized relationships among perceived value, awe, subjective wellbeing, religiosity, and donation intention.ResultsThe findings reveal that perceived value has a positive influence on donation intentions, both directly and indirectly, through awe and subjective wellbeing. Furthermore, religiosity significantly moderates these relationships, such that individuals with higher religiosity exhibit stronger effects of awe and subjective wellbeing on donation intentions.DiscussionBy incorporating the SOR framework, this study advances theoretical understanding of the psychological mechanisms underlying donation behavior in religious heritage tourism. The results suggest that enhancing tourists' emotional and spiritual experiences can strengthen their willingness to provide financial support, offering practical insights for heritage site managers seeking sustainable conservation strategies.